Process-based VOCs Source Profiles and Contributions to Ozone Formation in Typical Organic Solvent-used Industries in Hangzhou - Zhinian Li; Wenjuan Li; Rong Zhou; Xiaoping Miao; Jianhai Lu; Zhongren Wang; Zhongping Yang; Jian Wu (Aerosol and Air Quality Research)
Abstract The solvent-used industry plays an important role in volatile organic compounds (VOCs) emission, which has caused an increasing concern. Herein, VOCs samples collected before and after treatments from the painting industry, printing industry and printing & dyeing industry in Hangzhou were measured. Then, the VOCs removal efficiencies of different treatments were detailedly investigated. Among them, high-temperature incineration technology achieved the highest VOCs removal efficiency, averaging 93.0%. Process-based source profiles suggested that aromatics and alkanes accounted for more than 76.5% of VOCs, mainly including toluene, styrene, n-decane, n-undecane and n-dodecane. Furthermore, the ozone formation potentials (OFPs) based on processes suggested that toluene, meta-xylene, n-butene, styrene and ortho-xylene should be preferentially controlled to reduce the OFPs in painting industry and printing & dyeing industry. For printing industry, the contributions of top five species to the OFPs were relatively balanced, which indicated these species should all be given more attention. Finally, the low-temperature plasma technology and the combined technology of activated carbon adsorption with condensation were found to reduce the OFPs for their ability to preferably removing aromatics or olefins. The results were beneficial to develop effective VOCs abatement strategies and complemented the VOCs source profiles in solvent-used industries.